Data from renewable energy assessments for resort islands in the South China Sea - Basir Khan M.R.; Jidin R.; Pasupuleti J. (Elsevier Inc., 2023)
Hydroelectric power; Maps; Meteorology; Wind speed; Generation systems; Meteorological data; Microhydropower; PV system; Renewable energy assessments; Solar radiation,wind speed; South China sea; Wind energy generation; Wind energy generation system; Wind speed; Wind power